Comparative Analysis of Kidney Stone Composition in Patients from Ghana and South Africa: Case Study of Kidney Stones from Accra and Cape Town - Akpakli, Evans Ametefe (Department of Surgery, 2020)
Aim: The primary aim of this study was to describe and compare the kidney stone composition of kidney stone patients receiving treatment at the Korle-Bu Teaching Hospital (KBTH), Accra (Ghana) and Groote Schuur Hospital (GSH), Cape Town (South Africa). Methods: The study was a retrospective folder review of patients treated for kidney stone disease at the Korle-Bu Teaching Hospital in Accra (Ghana) and Groote Schuur Hospital in Cape Town (South Africa). Patients who were treated for kidney stone disease between 1st June 2016 and 31st May 2018 were recruited and their folder numbers were retrieved from theatre log books. A total of hundred and sixty-three (n=163) folders (n=30 KBTH; n=133 GSH) were subsequently retrieved from the records department of the two facilities. Demographic data and kidney stone analysis results were extracted and analyzed using the R statistical software. Results: The age of participants at the KBTH ranged from 24 to 75 years with a median age of 45 years, while the ages of participants at the GSH ranged between 19 to 77 years with a median age of 48 years. Males were the majority stone formers for both hospitals [56.7% KBTH; 59.4% GSH]. However, there was no significant statistical difference in gender (p=0.9447) and age (p=0.2612) between the two groups. Calcium oxalate (86.7%) and uric acid (90.0%) were the commonest components of the kidney stones analyzed from the KBTH. Calcium oxalate (66.2%) and carbonate apatite (40.6%) emerged as the most common components of the stones analyzed from the GSH. Brushite (3.0%), cystine (3.8%) and struvite (19.6%) stones were only found in the stones of participants receiving treatment at the GSH. All kidney stones from the KBTH were mixed; made up of at least two chemical components. Pure kidney stones were only found among the GSH dataset constituting 48.9% of all the stones analyzed. While all KBTH stones were mixed stones, female patients from GSH formed more mixed stones than their male counterparts (M:F = 40.5%:66.67%). Infection kidney stones (struvite and carbonate apatite) were also predominantly found among female stone formers in this study. Conclusion: The findings indicate that the participants from the two facilities are not different in terms of gender and age. However, the composition of stones was found to be different between participants from both hospitals. This suggests that that kidney stone composition may be influenced by patients’ geographical location and/or cultural background. Further studies with prospective or longitudinal data and larger samples are needed to provide more insight into the composition of kidney stones of African patients.